Solve for n -29+6n=6(6n+5)+1

Math
-29+6n=6(6n+5)+1
Simplify 6(6n+5)+1.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-29+6n=6(6n)+6⋅5+1
Multiply 6 by 6.
-29+6n=36n+6⋅5+1
Multiply 6 by 5.
-29+6n=36n+30+1
-29+6n=36n+30+1
Add 30 and 1.
-29+6n=36n+31
-29+6n=36n+31
Move all terms containing n to the left side of the equation.
Tap for more steps…
Subtract 36n from both sides of the equation.
-29+6n-36n=31
Subtract 36n from 6n.
-29-30n=31
-29-30n=31
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 29 to both sides of the equation.
-30n=31+29
Add 31 and 29.
-30n=60
-30n=60
Divide each term by -30 and simplify.
Tap for more steps…
Divide each term in -30n=60 by -30.
-30n-30=60-30
Cancel the common factor of -30.
Tap for more steps…
Cancel the common factor.
-30n-30=60-30
Divide n by 1.
n=60-30
n=60-30
Divide 60 by -30.
n=-2
n=-2
Solve for n -29+6n=6(6n+5)+1

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top